Absorption, transportation and distribution of imidacloprid in maize. Issue 8 (21st June 2017) - Sun, Donglei; Fu, Jiantao; Lu, Yinglin; Chen, Lijun; Gong, Hengliang; Zhao, Huanhuan; Dai, Sixing; An, Yuxing; Xu, Hanhong
ABSTRACT: The neonicotinoid imidacloprid is a very important insecticide in maize cultivation in China. A laboratory experiment was conducted to investigate its absorption, transportation and distribution in maize plants. Plants were exposed to an aqueous solution of imidacloprid at five concentrations (10, 20, 50, 100 and 200 μg/mL). The residues of imidacloprid in different plant parts were determined by using a quick and effective method of high-performance liquid chromatography. Results showed that the average recoveries ranged from 85.16% to 102.23%, with relative standard deviations of 1.82–4.40% at three different spiking levels in each different matrix. The half-lives of imidacloprid in hydroponic maize water were from 5.33 to 11.55 days. The concentrations in roots, stems and leaves were from 5.61 to 7.48, 1.03 to 4.03 and 0 to 30.57 μg/mL after 6 h–7 days exposed in 10 μg/mL imidacloprid aqueous solutions, respectively. Our study showed that imidacloprid was strongly absorbed by roots and mainly accumulated in leaves. Quantity ratio and bioconcentration factors (BCFs) were also used to estimate the distribution and accumulation in maize. The values of quantity ratios were the highest in the leaves while lowest in the root after 7 days treatments, with the ranking of leaves > stem > root. The BCFs were 0.63–1.66, 0.52–0.92 and 3.20–6.78 in root, stem and leaves, respectively. These results demonstrated that the exposed time and imidacloprid application concentrations were also the main factors influencing the absorption. This study enhances our understandings of the uptake and distribution of imidacloprid in maize plants.